STRUCTURE AND CATALYTIC RESIDUE PREDICTION OF A DEHALOGENASE FROM THE THIRD DOMAIN OF LIFE - ABUBAKAR, HASSANA; SALIHU, RABIU; NDATSU, YAKUBU; ALIYU OLALEKAN, AMUZAT; USMAN BOKO, HAMZA; MOHAMMED , HADIZA; LADIDI ABU, MARY (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Extreme archaea are known for their distinct molecular identities and production of enzymes with unique activities that have accorded them diverse applications. The amino acid sequence of most of these enzymes are deposited in the databank with unpredicted structures and domains. Here, the secondary structure, domain and three-dimensional structure of a dehalogenase from a halophilic archae was predicted employing GOR4, Pfam and four different modeling servers respectively. Model validation was performed in SAVES 06 based on Ramanchandran plot and ERRAT analysis. PyMOL sofware was used to visualize the model and superimpose it into the template. 45.93 % alpha helix, 15.85% extended strand and 38.21% random coil were the secondary structures predicted while HAD 2 was the only domain found in this enzyme. The SWISS-MODEL result was found to be the best model with the highest percentage of 92.9% residues in the most favoured region based on the Ramanchandran plot, and an overall quality factor of 97.196% in the ERRAT analysis. Aspartic acid was identified as essential catalytic residue. This structure prediction will help in the engineering of the enzyme for bioremediation application.